Preparation method and application of hollow nano square Mn1Fe3 PBA-coated NiFe LDH composite catalyst
By induced growth of Mn1Fe3 PBA nanocubes on the surface of NiFe LDH, the Mn1Fe3 PBA@NiFe LDH composite catalyst with hollow nanocube structure was formed, and the problems of low conductivity and stability of NiFe LDH electrocatalyst in OER were solved, achieving efficient and stable catalytic performance.
Patent Information
- Application Number
- CN202411824639.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing NiFe LDH electrocatalysts have problems such as low electron conductivity, slow kinetics and poor stability in oxygen precipitation reaction (OER), which limits their application.
The Mn1Fe3 PBA@NiFe LDH composite catalyst with hollow nanocube structure was prepared by solution precipitation method and hydrothermal method. The Mn1Fe3 PBA nanocube was induced to grow Mn1Fe3 PBA nanocubes on the surface of NiFe LDH to form a three-dimensional hollow nanocube structure.
The electronic conductivity, catalytic activity and stability of the catalyst are significantly improved, the overpotential is reduced, the service life of the electrocatalyst is extended, and the chemical stability is shown in alkaline media.
Smart Images

Figure CN119776885A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a preparation method and application of a hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst. Background Art
[0002] With the increasing consumption of non-renewable fossil fuels and the resulting environmental degradation, the development of new energy sources has become crucial. Electrocatalysis is considered to be one of the most promising options to provide clean and renewable energy and solve global environmental pollution and energy problems. The oxygen evolution reaction (OER), as one of the half-reactions of the electrochemical water splitting process, is more energetic than the hydrogen evolution reaction (HER) due to the inherently slow kinetics of multi-step proton-coupled electron transfer. Although noble metal catalysts such as RuO2 and IrO2 have high OER activity, their limited availability and high cost hinder their widespread application. Therefore, it is imperative to explore potential oxygen evolution reaction catalysts with good catalytic activity and low cost.
[0003] To this end, a lot of efforts have been made to design and synthesize various non-precious metals and their derivatives as efficient OER electrocatalysts. Among them, NiFe LDH is the most widely used, but the NiFe LDH electrocatalyst has the characteristics of low electronic conductivity, slow kinetics, and poor stability, which limits its application in OER. The low electronic conductivity originates from the layered structure of NiFe, and the weak connection between the layers limits the electron transfer perpendicular to the layers. Therefore, improving the interaction between the layers is an important task. This paper proposes an effective method to improve the conductivity of NiFe LDH. In addition, the contact resistance between NiFe LDH and the electrode is very large, so the selection of appropriate self-supporting electrodes is very important to eliminate the contact resistance.
[0004] Combining conventional LDH with other active materials is a simple way to improve the OER activity of LDH. Metal-organic frameworks (MOFs) are a new class of highly porous crystalline materials with huge surface areas, which can provide abundant electrocatalytically active metal sites and promote charge / mass transfer. Due to their inherent advantages, including high porosity and the ability to flexibly design their composition and structure, transition metal-based MOFs have become promising low-cost OER catalysts. Prussian blue analogs (PBAs) are a special type of MOF that also have the metal center tunability and porous characteristics of MOFs, which makes it easier to patch and change their internal spatial structure. In addition, PBAs have recently attracted attention as OER electrocatalysts due to their water stability, porosity, crystallinity, and redox-active metal centers. PBAs can not only act on OER catalytic active sites, but also directly provide mass transfer channels in the range of 150 to 200 nm. At the same time, LDH, which has also been studied as an OER catalyst, has micron-nanoscale mass transfer channels generated by the hydrangea structure. Especially when loaded on highly conductive nickel foam (NF) with three-dimensional porosity and well-defined internal space, the diffusion transport distance of active substances and charges can be significantly shortened and the two-phase mass transfer efficiency can be improved. Summary of the invention
[0005] In view of the above problems, the present invention aims to provide a method for preparing a hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst to improve the efficiency of the oxygen evolution reaction and the stability of the catalyst, so as to reduce the overpotential, improve the catalytic activity and extend the service life of the electrocatalyst.
[0006] The technical solution of the present invention is as follows:
[0007] On the one hand, the present invention provides a method for preparing a hollow nano-cube Mn1Fe3PBA@NiFeLDH composite catalyst. The composite catalyst adopts a substrate material, prepares Mn1Fe3PBA nanocubes by a solution precipitation method, prepares NiFeLDH hydrangea by a hydrothermal method, and combines the Mn1Fe3PBA nanocubes and the NiFeLDH hydrangea to form a Mn1Fe3PBA@NiFeLDH composite catalyst with a three-dimensional hollow nano-cube structure.
[0008] Furthermore, the preparation of the substrate material specifically includes the following steps: 2 The nickel foam is sequentially placed in a 1.0 M hydrochloric acid solution, an acetone solution, anhydrous ethanol and deionized water for ultrasonic treatment to remove surface impurities and an oxide layer, and then placed in a vacuum drying oven at 60° C. for 30 minutes to obtain the substrate material.
[0009] Furthermore, the process of preparing Mn1Fe3PBA nanocubes by solution precipitation method specifically includes the following steps: dissolving a divalent manganese salt in a mixed solution of deionized water and ethanol and stirring to obtain a transparent solution A, and then dissolving a trivalent iron salt in deionized water and ethanol and stirring to obtain a transparent solution B; then adding PVP to the transparent solution B and stirring evenly to obtain a transparent solution C, slowly dripping the transparent solution A into the transparent solution C under vigorous stirring and stirring to obtain a mixed solution, placing the substrate material in the mixed solution and incubating at room temperature, washing and drying to obtain the Mn1Fe3PBA nanocubes.
[0010] Furthermore, the divalent manganese salt is one or more of manganese sulfate monohydrate, manganese chloride, and manganese carbonate, and the trivalent iron salt is one or more of ferric sulfate, ferric chloride, ferric nitrate, and potassium ferrocyanide.
[0011] Furthermore, the molar ratio of the manganese ions in the divalent manganese salt to the iron ions in the trivalent iron salt is 1-3:1-3.
[0012] Furthermore, the molar ratio of the manganese ions in the divalent manganese salt to the iron ions in the trivalent iron salt is 1:3.
[0013] Furthermore, the process of preparing NiFeLDH hydrangea by hydrothermal method specifically includes the following steps: adding a nickel source, an iron source, urea and ammonium fluoride to deionized water and stirring to mix well to obtain a reaction solution; adding a base material to the reaction solution for a hydrothermal reaction; collecting the precipitated product of the hydrothermal reaction, washing and drying to obtain NiFeLDH hydrangea.
[0014] Furthermore, the temperature of the hydrothermal reaction is 120° C. and the reaction time is 7 h.
[0015] Furthermore, the preparation of the composite catalyst specifically includes the following steps: placing NiFeLDH hydrangea into the mixed solution, incubating at room temperature to obtain black nickel foam, and washing and drying the black nickel foam to obtain the Mn1Fe3PBA nanocube@NiFeLDH composite catalyst.
[0016] On the other hand, a hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst is provided for use in alkaline anode oxygen evolution reaction.
[0017] The beneficial effects of the present invention are:
[0018] 1. The present invention proposes a new method for preparing a Mn1Fe3 PBA@NiFe LDH composite catalyst, which adopts a hydrothermal method and a solution precipitation method, and uses Ni salt, Fe salt and Mn salt to replace the traditional precious metal catalyst, thereby significantly reducing the preparation cost and simplifying the preparation process. The catalyst prepared by this method is not only low in cost, but also simple in preparation process.
[0019] 2. The present invention prepares a Mn1Fe3 PBA@NiFe LDH composite catalyst with a hollow block structure by a hydrothermal method and a solution precipitation method. The catalyst uses NiFe LDH as a substrate and induces the growth of nano-cubic Mn1Fe3 PBA on the surface of NiFe LDH by a solution precipitation method, forming an electrocatalyst with excellent microstructure and catalytic performance. This catalyst not only has high conductivity, high activity and good stability, but also its unique three-dimensional (3D) hollow block structure provides a large specific surface area, ensuring full exposure of adsorption sites and active sites. In alkaline media, the catalyst exhibits higher chemical stability. Thanks to the synergistic effect of the two components and the unique heterogeneous structure, the accessibility of the electrolyte to the internal active centers is improved, thereby showing excellent electrocatalytic performance in the OER reaction.
[0020] 3. The present invention also constructs an in-situ dual-scale porous structure in the Mn1Fe3 PBA@NiFe LDH catalyst. This structure includes Mn1Fe3 PBA nanocubes, NiFe LDH hydrangeas, and nickel foam (NF) skeletons, which provide pores of hundreds of nanometers, micrometers to nanometers, and hundreds of micrometers, respectively. The successful construction of this hierarchical mass transfer channel makes the OER performance of the catalyst more excellent, emphasizes the importance of suitable mass transfer channels, and provides potential for the Mn1Fe3 PBA@NiFe LDH catalyst in industrial-scale applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Preparation flow chart of the Mn1Fe3 PBA@NiFe LDH composite catalyst according to an embodiment of the present invention;
[0022] Figure 2 is the X-ray diffraction spectrum of NiFe LDH prepared in Example 1 of the present invention;
[0023] Figure 3 X-ray diffraction spectra of Mn1Fe3 PBA and Mn1Fe3 PBA@NiFe LDH prepared in Example 1 of the present invention;
[0024] Figure 4 This is a scanning electron microscope image of the NiFe LDH prepared in Example 1 of the present invention;
[0025] Figure 5 is a scanning electron microscope image of Mn1Fe3 PBA prepared in Example 1 of the present invention;
[0026] Figure 6 This is an energy dispersive X-ray spectrum image of Mn1Fe3 PBA prepared in Example 1 of the present invention;
[0027] Figure 7 This is a scanning electron microscope image of the Mn1Fe3 PBA@NiFe LDH prepared in Example 1 of the present invention;
[0028] Figure 8 Linear sweep voltammetry curves of Mn1Fe3 PBA, Mn2Fe2 PBA and Mn3Fe1PBA samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;
[0029] Fig. 9 Polarization curves of NF, Mn1Fe3 PBA, NiFe LDH and Mn1Fe3 PBA@NiFe LDH samples prepared in Example 1 of the present invention;
[0030] Fig.10 The Tafel plots of NF, Mn1Fe3 PBA, NiFe LDH and Mn1Fe3 PBA@NiFe LDH samples prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with the accompanying drawings and examples, but it is not intended to limit the scope of the present invention, and is only illustrative. It should be noted that, in the absence of conflict, the embodiments in the present application and the technical features in the embodiments can be combined with each other. Unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those of ordinary skill in the art to which this application belongs. The experimental methods used in the following examples are conventional methods unless otherwise specified. Materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.
[0032] Example 1
[0033] A hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst is prepared by the following steps. The preparation flow chart is as follows: Figure 1 As shown:
[0034] (1) Preparation of substrate material: 1*1cm 2 The nickel foam was placed in 1.0 M hydrochloric acid solution, 1.0 M acetone solution, 1.0 M anhydrous ethanol and 1.0 M deionized water for ultrasonic treatment in turn. After the treatment, it was placed in a vacuum drying oven at 60°C for 30 min.
[0035] (2) Preparation of Mn1Fe3 PBA: 1 mmol of MnSO4·H2O was dissolved in 20 ml of deionized water and 20 ml of ethanol solution and stirred to obtain a transparent solution A. Then 3 mmol of K3[Fe(CN)6]·H2O was dissolved in 20 ml of deionized water and 20 ml of ethanol solution and stirred to obtain a transparent solution B. Then 2 g of PVP was added to the transparent solution B and stirred until uniform to obtain a transparent solution C. Under vigorous stirring, the transparent solution A was slowly dripped into the transparent solution C and stirred for 30 min to obtain a mixed solution. The nickel foam substrate (NF) was placed in the mixed solution and incubated at room temperature for 24 h to obtain a black NF. Finally, the black NF was washed with anhydrous ethanol and dried at 60°C for 5 hours to obtain Mn1Fe3 PBA nanocubes, and the product was recorded as Mn1Fe3 PBA.
[0036] (3) Preparation of NiFe LDH: NiFe LDH hydrangea was prepared by hydrothermal method. 0.096 g Ni(NO3)2·6H2O, 0.189 g Fe(NO3)2·9H2O, 20 mmol urea and 8 mmol NH4F were dissolved in 60 mL deionized water and stirred at room temperature for 30 min. 2 The NFs were transferred together into a 100 mL Teflon-lined reactor and subjected to hydrothermal reaction at 120 °C for 7 h to obtain yellow NFs. The yellow NFs were repeatedly rinsed with water and ethanol for 3 times and dried at 60 °C for 5 h to obtain NiFe LDH hydrangea.
[0037] (4) Preparation of Mn1Fe3 PBA@NiFe LDH composite catalyst: 1mmol of MnSO4·H2O was dissolved in 20ml of deionized water and 20ml of ethanol solution and stirred to obtain transparent solution A. Then 3mmol of K3[Fe(CN)6]·H2O was dissolved in 20ml of deionized water and 20ml of ethanol and stirred to obtain transparent solution B. Then 2g of PVP was added to transparent solution B and stirred until uniform to obtain transparent solution C. Under vigorous stirring, transparent solution A was slowly dripped into transparent solution C and stirred for 30min to obtain a mixed solution. The prepared NiFe LDH hydrangea was placed in the mixed solution and incubated at room temperature for 24h to obtain black NF. Finally, the black NF was washed 3 times with anhydrous ethanol and deionized water and dried at 60℃ for 5 hours to obtain the desired product Mn1Fe3PBA@NiFe LDH composite catalyst.
[0038] Comparative Example 1
[0039] 2mmol of MnSO4·H2O was dissolved in 20ml of deionized water and 20ml of ethanol solution and stirred to obtain a transparent solution D. Then 2mmol of K3[Fe(CN)6]·H2O was dissolved in 20ml of deionized water and 20ml of ethanol solution and stirred to obtain a transparent solution E. Then 2g of PVP was added to the transparent solution E and stirred until uniform to obtain a transparent solution F. Under vigorous stirring, the transparent solution D was slowly dripped into the transparent solution F and stirred for 30min to obtain a mixed solution. The foamed nickel substrate material (NF) was placed in the mixed solution and incubated at room temperature for 24h. Finally, the black NF after the reaction was washed with anhydrous ethanol and dried at 60℃ for 5 hours. The product was recorded as Mn2Fe2 PBA.
[0040] Comparative Example 2
[0041] 3mmol of MnSO4.H2O was dissolved in 20ml of deionized water and 20ml of ethanol solution and stirred to obtain a transparent solution G. Then 1mmol of K3[Fe(CN)6].H2O was dissolved in 20ml of deionized water and 20ml of ethanol solution and stirred to obtain a transparent solution H. Then 2g of PVP was added to the transparent solution B and stirred until uniform to obtain a transparent solution I. Under vigorous stirring, the transparent solution G was slowly dripped into the transparent solution I and stirred for 30min to obtain a mixed solution. The foamed nickel substrate material (NF) was placed in the mixed solution and incubated at room temperature for 24h. Finally, the black NF after the reaction was washed with anhydrous ethanol and dried at 60°C for 5 hours to obtain a product recorded as Mn2Fe2 PBA.
[0042] Based on the above embodiments, the following experiments were conducted:
[0043] 1. X-ray diffraction experiment of NiFe LDH
[0044] Taking the NiFe LDH prepared in Example 1 as an example, the NiFe LDH was subjected to X-ray diffraction (XRD), and the results are as follows: Figure 2 As shown, the phase of the catalyst was determined by XRD analysis. Figure 2 The diffraction peaks of the nanostructured carbon nanotubes were consistent with those of the NiFe LDH standard card (JCPDS No.40-0215), indicating that NiFe LDH was successfully synthesized on the NF.
[0045] 2. X-ray diffraction experiments of Mn1Fe3 PBA and Mn1Fe3 PBA@NiFe LDH
[0046] Taking the Mn1Fe3 PBA and Mn1Fe3 PBA@NiFe LDH prepared in Example 1 as examples, X-ray diffraction analysis was performed on Mn1Fe3 PBA and Mn1Fe3 PBA@NiFe LDH. The results are as follows: Figure 3As shown, the XRD pattern shows that after the growth of Mn1Fe3 PBA, the diffraction peak belonging to Mn1Fe3 PBA (JCPDS No.97-041-6994) appears, while the diffraction peak belonging to NiFe LDH still exists, indicating the successful formation of this heterogeneous structure.
[0047] 3. Scanning electron microscopy experiment of NiFe LDH
[0048] Taking the NiFe LDH prepared in Example 1 as an example, a scanning electron microscope (SEM) experiment was performed on the NiFe LDH, and the results are as follows: Figure 4 As shown in the figure, it can be seen that NiFe LDH grows evenly on the NF surface, presenting a uniform hydrangea-like nanosheet structure.
[0049] 4. SEM experiment of Mn1Fe3 PBA
[0050] Taking the Mn1Fe3 PBA prepared in Example 1 as an example, a scanning electron microscope experiment was performed on the Mn1Fe3 PBA. The results are as follows: Figure 5 As shown in the figure, it can be seen that Mn1Fe3 PBA grows evenly on the NF surface and presents a uniform nano-square structure.
[0051] 5. X-ray energy spectrum analysis experiment of Mn1Fe3 PBA
[0052] Taking the Mn1Fe3 PBA prepared in Example 1 as an example, the Mn1Fe3 PBA was subjected to X-ray energy spectrum analysis (EDS), and the results are as follows: Figure 6 As shown, its element distribution is shown in the figure. It can be found that the main elements of the catalyst are Mn, Fe, O and S, which are consistent with the raw material composition used in catalyst preparation, and it can be observed from the color that the element distribution is very uniform.
[0053] 6. SEM experiment of Mn1Fe3 PBA@NiFe LDH
[0054] Taking the Mn1Fe3 PBA@NiFe LDH prepared in Example as an example, a scanning electron microscope experiment was performed on the Mn1Fe3 PBA@NiFe LDH. The results are as follows: Figure 7As shown in the figure, it can be seen that after the composite, the hydrangea is transformed into a hollow nanocube. PBA grows along the lamellar structure of LDH and eventually transforms from a lamellar structure into a stacked nanocube. The nanosheets are uneven during the growth process and form a hollow structure. In this way, not only a nanocubic structure but also a hollow defect is formed in Mn1Fe3 PBA@NiFe LDH. Considering the pores of the NF skeleton at the scale of hundreds of microns, a dual-scale porous structure is successfully constructed in Mn1Fe3 PBA@NiFe LDH, achieving smooth mass transfer.
[0055] VII. Linear Sweep Voltammetry Experiments of Different PBA Samples
[0056] Taking the PBA samples prepared in Example 1, Comparative Example 1 and Comparative Example 2 as examples, linear sweep voltammetry (LSV) experiments were performed on Mn1Fe3 PBA, Mn2Fe2 PBA and Mn3Fe1 PBA, respectively. The results are as follows: Figure 8 As shown in Figure 2, the effect of different molar ratios of Mn:Fe on the electrocatalytic activity of PBA samples prepared by Figure 8 It can be seen that the best OER activity is shown when the molar ratio of Mn:Fe is 1:3.
[0057] 8. Linear Sweep Voltammetry Experiments of Different Samples
[0058] The NF, Mn1Fe3 PBA, NiFe LDH and Mn1Fe3 PBA@NiFe LDH prepared in Example 1 were used as samples, and a 1.0M KOH solution was prepared. Specifically, 16.833 g of KOH was weighed and placed in a 500 mL beaker, and 300 mL of deionized water was added and ultrasonically vibrated to form a uniform solution. After the samples were prepared, they were placed in a 1.0 M KOH solution, and the electrochemical properties were tested by linear sweep voltammetry (LSV) using a three-electrode system.
[0059] In order to explore the effect of PBA and LDH composite on the electrochemical performance of the material, LSV technique was used to compare the scanning rate of 1mV s -1 Electrochemical OER performance of the samples. The OER performance was evaluated with 1 M KOH: Fig. 9 Polarization curves of NF, Mn1Fe3PBA, NiFe LDH and Mn1Fe3 PBA@NiFe LDH samples; Compared with NiFe LDH, Mn1Fe3 PBA and NF, Mn1Fe3 PBA@NiFe LDH sample exhibits the best OER activity, indicating that the composite of layered structure and metal organic framework can effectively improve the OER catalytic activity. Only 225mV overpotential is needed to reach 10mAcm -2This is lower than the 250 mV of the NiFe LDH catalyst. Fig.10 The Tafel plots of NF, Mn1Fe3 PBA, NiFe LDH and Mn1Fe3 PBA@NiFe LDH samples are used for kinetic comparison of the catalysts. -2 The Tafel slope at is 46.4mV dec -1 , compared with NiFe LDH (60.1mV dec -1 ) compared to the conventional kinetics.
[0060] The introduction of Mn can improve the electronic conductivity and electrochemical performance of Prussian blue analogs (PBA). Studies have shown that the doping of Mn and Fe can not only improve the conductivity but also activate the key H2O deprotonation step. According to Gibbs free energy calculations, the charge depletion of Mn atoms can greatly enhance the adsorption of electron-rich oxygen-containing groups on the surface, which is beneficial for the adsorption and conversion of intermediates in the OER process. The active sites (Mn, Fe and C) of Mn1Fe3 PBA can all adsorb and desorb *OOH, OH and O, thereby accelerating the conversion of intermediates and increasing the OER rate. Since the electronegativity of Mn is lower than that of Fe, Mn has a moderate binding strength with the adsorbed oxygen-containing intermediates, which may be due to the better OER activity. The transition metal Mn can not only act as an electronic additive to provide electrons to the iron phase and promote the reduction of the iron system, but also act as a structural additive to promote the dispersion of the active phase, which has the advantage of improving the reaction activity of the catalyst.
[0061] In summary, the introduction of Mn in OER can improve electronic conductivity, enhance the adsorption of oxygen-containing groups, accelerate the conversion of intermediates, reduce overpotential, increase the theoretical overpotential of active sites, moderately bind oxygen-containing intermediates, and improve catalyst reactivity, which are all key factors for improving OER performance.
[0062] Mn1Fe3 PBA (manganese iron Prussian blue analog) exhibits higher electronic conductivity. This is because the synergistic effect between different metal atoms improves electronic conductivity and increases specific surface area and electrochemical activity. Mn1Fe3 PBA can alleviate the volume effect by separating into monometallic compounds during the insertion / deinsertion of sodium and potassium ions, thereby improving structural stability. Mn Fe PBA has a higher redox potential, which helps to improve the energy density of the battery. MnFe PBA has Mn 3+ / Mn 2+ and Fe 3+ / Fe 2+Two active sites participate in the redox reaction. The introduction of Mn element can reduce the defects in the PBA framework, thereby improving the stability of the material. MnFePBA as an anode catalyst for oxygen evolution reaction provides a wider operating voltage range, which is beneficial for practical applications.
[0063] In summary, MnFe PBA exhibits more advantages in electronic conductivity, structural stability, and redox potential, especially in improving OER performance and stability, MnFe PBA provides more benefits.
[0064] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst, characterized in that: The composite catalyst adopts a base material, prepares Mn1Fe3 PBA nanocubes by a solution precipitation method, prepares NiFe LDH hydrangea by a hydrothermal method, and combines the Mn1Fe3 PBA nanocubes and the NiFe LDH hydrangea to form a Mn1Fe3 PBA@NiFe LDH composite catalyst with a three-dimensional hollow nanocube structure.
2. The method for preparing the hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst according to claim 1, characterized in that: The preparation of the substrate material specifically includes the following steps: 2 The nickel foam is sequentially placed in a 1.0 M hydrochloric acid solution, an acetone solution, anhydrous ethanol and deionized water for ultrasonic treatment to remove surface impurities and an oxide layer, and then placed in a vacuum drying oven at 60° C. for 30 minutes to obtain the substrate material.
3. The method for preparing the hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst according to claim 1, characterized in that: The process of preparing Mn1Fe3 PBA nanocubes by solution precipitation method specifically includes the following steps: dissolving a divalent manganese salt in a mixed solution of deionized water and ethanol and stirring to obtain a transparent solution A, then dissolving a trivalent iron salt in deionized water and ethanol and stirring to obtain a transparent solution B; then adding PVP to the transparent solution B and stirring evenly to obtain a transparent solution C, slowly dropping the transparent solution A into the transparent solution C under vigorous stirring and stirring to obtain a mixed solution, placing a substrate material in the mixed solution and incubating at room temperature, washing and drying to obtain the Mn1Fe3 PBA nanocubes.
4. The method for preparing the hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst according to claim 3, characterized in that: The divalent manganese salt is one or more of manganese sulfate monohydrate, manganese chloride, and manganese carbonate, and the trivalent iron salt is one or more of ferric sulfate, ferric chloride, ferric nitrate, and potassium ferrocyanide.
5. The method for preparing the hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst according to claim 3, characterized in that: The molar ratio of the manganese ions in the divalent manganese salt to the iron ions in the trivalent iron salt is 1-3:1-3.
6. The method for preparing the hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst according to claim 5, characterized in that: The molar ratio of the manganese ions in the divalent manganese salt to the iron ions in the trivalent iron salt is 1:
3.
7. The method for preparing the hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst according to any one of claims 1 to 6, characterized in that: The process of preparing NiFe LDH hydrangea by hydrothermal method specifically includes the following steps: adding a nickel source, an iron source, urea and ammonium fluoride into deionized water and stirring to mix well to obtain a reaction solution; adding a substrate material into the reaction solution to perform a hydrothermal reaction; collecting the precipitated product of the hydrothermal reaction, washing and drying to obtain the NiFe LDH hydrangea.
8. The method for preparing the hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst according to claim 7, characterized in that: The temperature of the hydrothermal reaction is 120° C. and the reaction time is 7 h.
9. The method for preparing the hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst according to claim 3, characterized in that: The preparation of the composite catalyst specifically includes the following steps: placing NiFe LDH hydrangea into the mixed solution, incubating at room temperature to obtain black nickel foam, and washing and drying the black nickel foam to obtain the Mn1Fe3 PBA nanocube@NiFe LDH composite catalyst.
10. Use of the hollow nano-block Mn1Fe3 PBA@NiFe LDH composite catalyst according to claim 1 in alkaline anode oxygen evolution reaction.
Citation Information
Patent Citations
In-situ preparation method of two-dimensional Prussian blue analogue @ MXene composite electrocatalyst
CN112058286A
Preparation method and application of surface-modified nano iron-manganese composite catalyst
CN113578365A
Cited By
Ru-modified NiFe-based layered double hydroxide based on defect regulation and control as well as preparation method and application of Ru-modified NiFe-based layered double hydroxide
CN122428325A